Palynological Investigation of Echium italicum, E. plantagineum and E. glomeratum Species Distributed in Türkiye - Gencal, Melek; Doğan, Gülden; Kıran, Yaşar; Demirpolat, Azize (Uğur ÇAKILCIOĞLU, 2025)
In this study, genera of Echium from the family Boraginaceae, Echium italicum, Echium plantagineum and Echium glomeratum taxa the morphologies of the pollen were revealed using light microscopy (LM) and scanning electron microscopy (SEM). According to the research results, the symmetry, aperture, and ornamentation in the pollens of the species generally show similarities. All the pollens examined were heteropolar symmetry and aperture type tricolpate, while in two of the three species investigated, the pollen grains were subprolate, whereas in the remaining species they were prolate. In polar view, the broader pole exhibits a rounded–triangular outline, while the narrower pole is characterized by a more deeply incised, three-lobed configuration. In equatorial view, pollen shape ranges from ovoid to ovoid–triangular. Exine ornamentation is generally reticulate the pollen surface, but appears distinctly granulate within the colpus region.
Keywords: Botany (Other); Bitki Bilimi (Diğer)